Policies and tools planners use to support pedestrian-oriented downtowns in North Texas - Matthews, Mara (My University, 2026)
Suburban downtowns in North Texas have been shaped by car-centric development for decades, making walking or biking anywhere inconvenient and uncomfortable for daily travel. This report looks at how three North Dallas suburbs, Allen, Frisco, and McKinney, are using planning policies, design tools, and different economic strategies to help shift more towards pedestrian-oriented downtowns. Using an approach that looks at planning documents and interviews with city planners, the study identifies priorities that all three cities share, like street design, community engagement, and making the downtowns in these cities more connected. While each of the cities is on different steps of the implementation process, it is clear that there is momentum and excitement towards designing for people before cars, even with the suburban culture with expectations of car convenience. This report concludes by giving recommendations for deepening public health considerations when it comes to pedestrian-oriented development, and more recommendations about how North Dallas suburbs can better their downtown development.
Keywords: Downtown planning; Pedestrian-oriented downtowns; Public health